Ecoliteracy Competency Factors for Prospective Elementary School Teachers in Green Campus Policy - Permata, Santy Dinar; Untari, Esti; Ni Luh Sakinah Nuraini; Aura, Nurlyta Bintang; Maulidha, Arini Putri; Mimah, Sri Suryani; Rahmita, Sulvi Nuke (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The purpose of this study is to identify and describe the structure of eco-literacy factors possessed by prospective elementary school teachers within the framework of green campus policy implementation. The study focuses on integrating cognitive, affective, and psychomotor dimensions. Methodology: A descriptive quantitative approach was applied using Exploratory Factor Analysis (EFA). The study included 317 respondents. These respondents were students majoring in elementary school teacher education who had completed elementary school science education courses. The instrument was an eco-literacy questionnaire with 45 statements rated on a Likert scale. Data analysis was performed using SPSS with Principal Component Analysis and Varimax rotation. Main Findings: The analysis results found a KMO value of 0.830 and a significant Bartlett test (Sig.=0.001). These results indicate that the data is suitable for further processing. Four factors were identified, accounting for 57.379% of the total variance, covering awareness and understanding of ecological concepts, attitudes and values of ecological literacy, environmentally conscious behavior, and the integration of ecological values into daily life. Novelty/Originality of this study: The findings reveal a multidimensional and integrative structure of ecoliteracy skills. The results also show a clear connection among the cognitive, affective, and psychomotor domains. The resulting factor model can serve as a conceptual basis for strengthening sustainability-oriented didactic content knowledge in the design of green curricula for elementary school teacher education.